2015
DOI: 10.1002/jcla.21836
|View full text |Cite
|
Sign up to set email alerts
|

Serum Adenosine Deaminase (ADA) Activity: A Novel Screening Test to Differentiate HIV Monoinfection From HIV‐HBV and HIV‐HCV Coinfections

Abstract: We showed strong agreement and correlation between CD4(+) cell count and ADA enzyme activity. Based on high ADA sensitivity and specificity, it is concluded that determination of ADA activity might be a novel diagnostic tool to distinguish of HIV monoinfection from its coinfection with HBV or HCV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 18 publications
1
9
0
2
Order By: Relevance
“…In the study of Chilo L. et al, CD4 counts of patients with HIV/HBV infection were significantly lower than mono-infected patients (30). Another study also demonstrated low amount of CD4 cells in co-infected patients (31). In the present study, the mean number of CD4 cells in patients was 120 (cells/μL).…”
Section: Discussionsupporting
confidence: 55%
“…In the study of Chilo L. et al, CD4 counts of patients with HIV/HBV infection were significantly lower than mono-infected patients (30). Another study also demonstrated low amount of CD4 cells in co-infected patients (31). In the present study, the mean number of CD4 cells in patients was 120 (cells/μL).…”
Section: Discussionsupporting
confidence: 55%
“…Deficiency of ADA activity is associated with defects related to immunological development, which can result in hematologic malignancies (Li, Nakagome, Hirono, Itoh, & Fujiwara, 2015). However, high levels of ADA in serum are associated with hepatic diseases (Abdi et al, 2016;Torgutalp, Efe, Babaoglu, & Kav, 2017). Serum ADA activity is also significantly increased in patients with chronic hepatitis, cirrhosis, and hepatocellular carcinoma, and thus this factor can be used as a screening index for chronic liver disease.…”
Section: Meijermentioning
confidence: 99%
“…HIV infection disturbs CD26/ADA costimulation, highjacks the immunomodulatory actions of Treg cells, and stimulates the generation of adenosine [108], in addition to downregulate ADA expression in lymphocytes [86]. In contrast, ADA enzymatic activity is reportedly increased in serum [103,104,[115][116][117][118][119][120] and plasma of HIV patients [121][122][123] to overcome the effects of excessive adenosine levels.…”
Section: Ada In the Context Of Hiv Pathogenesismentioning
confidence: 99%
“…ADA activity in HIV patients has long been evaluated in serum and plasma [121][122][123] lymphocytes [124], erythrocytes [125,126], and platelets [71]. Correlations between ADA activity and several clinical parameters such as seroconversion [121,126], prognosis [84, 97-100, 104, 107], immune activation [118], CD4 + T cell count [115,[118][119][120]123], viral load [118], CD4/CD8 ratio [119], coinfection [115,120], and treatment outcome [71,117,119,123] are discussed. Most of these studies aimed to use ADA activity as a biomarker but also helped to understand the pathological processes involved in the infection.…”
Section: Ada In the Context Of Hiv Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation